Case Report: Suprachoroidal Hemorrhage after Chiropractic Manipulation of the Neck. Issue 7 (July 2020) - El Hamichi, Sophia; Graversen, Veronica Kon; Gold, Aaron S.; Latiff, Azeema; Murray, Timothy G.
Abstract : SIGNIFICANCE: The case report highlights the possible complications of undergoing neck manipulation within a critical time period after intravitreal injection. PURPOSE: This study aimed to describe a case of traumatic hemorrhagic choroidal detachment after cervical manipulation during a chiropractic treatment session. CASE REPORT: A 43-year-old male patient with a history of complex rhegmatogenous retinal detachment repair and recurrent cystoid macular edema presented with decreased vision and sudden pain in the right eye after chiropractic manipulation of the neck, status post-intravitreal injection of triamcinolone, which was performed earlier that day. Vision in the right eye was hand motion and 20/20 in the left eye. IOPs were 8 and 11 mmHg, respectively. Slit lamp examination of the right eye revealed blood-tinged steroid residues in the anterior chamber. There was no view to the posterior pole. Ultrasonography showed a lobulated mass with heterogeneous echogenicity consistent with a large hemorrhagic choroidal detachment. No central kissing was observed. Left eye examination was unremarkable. CONCLUSIONS: With the increasing use of complementary and alternative medicine, a better understanding of potential complications to raise awareness is becoming essential.